In vitro neutralization of equid herpesvirus 1 mediated by recombinant antibodies - Molinková, Dobromila; Skládal, Petr; Celer, Vladimír (Journal of immunological methods, 2008)
A phage antibody display library of single chain fragment variables (scFv) was applied to develop anti-equid herpesvirus-1 (EHV-1) glycoprotein D (gD) neutralizing antibodies. To enrich for specific scFvs, the phage antibody library was panned against epitope derived from the N-terminal part of EHV-1 gD. Unique clones were differentiated by BstNI fingerprinting and further characterized by sequencing and immunoreactivity. The neutralizing effect of each clone was assessed by plaque reduction assay. Three clones with neutralizing effect were isolated.
Keywords: financování organizované; Animals; Peptide Library; Kinetics; buněčné linie; Immunoglobulin Variable Region; Microscopy, Fluorescence; Viral Envelope Proteins; imunoglobuliny - fragmenty; Viral Plaque Assay; sekvence aminokyselin; nemoci koní; Molecular Sequence Data; rekombinantní proteiny; Recombinant Proteins; Herpesvirus 1, Equid; Amino Acid Sequence; fluorescenční mikroskopie; koně; Immunoblotting; Cell Line; Horses; Herpesviridae Infections; Financing, Organized; molekulární sekvence - údaje; proteiny virového obalu; herpesvirus 1 koní; plakové testy; peptidová knihovna; Immunoglobulin Fragments; herpetické infekce; imunoblotting; zvířata; kinetika; Horse Diseases; variabilní oblast imunoglobulinu